THE CHALLENGE OF WORKING FROM HOME FOR DUAL CAREER COUPLES JAVA ETHNIC - Haifa Hannum Arija; Mirwan Surya Perdhana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The implementation of the policy of working from home during the Covid-19 pandemic has an impact on dual career couples where they are faced with challenges because they are in a new situation. The cultural background of each individual is also thought to influence how they face these challenges. This is because previous research has shown that Western cultural values tend to be suitable in implementing this policy. This study investigates the challenges faced by Javanese ethnic dual career couples and how they deal with them. Therefore mixed methods were used to achieve the research objectives. The respondents of this study were 5 married couples, or 10 individuals, from dual career couples backgrounds. The results found that the role of Javanese ethnic wives was more challenging to work from home. Keywords: Working from Home, Dual Career Couples, Cultural Values.